2021
DOI: 10.1186/s13018-021-02777-9
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of loaded sPL sustained-release microspheres inhibits osteoarthritis and promotes cartilaginous repairs

Abstract: Background Osteoarthritis is a chronic inflammatory disease of the joints associated with significant morbidity and lower quality of life. Current treatment strategies focus on reducing cartilage degeneration but fail to restore their proliferative ability. Super-activated platelet lysate (sPL) is an enhanced form of platelet-rich plasma that can be easily inactivated. The purpose of this study is to evaluate whether sPL-loaded PLGA/chitosan/gelatin microspheres can prevent and treat osteoarthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“… Preparative ​technique Merits Demerits Application Microsphere-drug ​combination Ref. Emulsion-solidication Large-scale production, simple operation Wide particle size Oncotherapy Neuralrepair TPP/chitosan/PLGA-NGF Microspheres 5-Fluorouracil loaded biodegradable magnetic Microspheres Polysaccharidebased porous microsphere (PPM) [ 88 , 188 , 189 ] Microfluidics Unique analytical performance, smaller volume, good monodispersity Low production efficiency Oncotherapy 5-Fu loaded CS microspheres [ 30 , 35 ] Mold method Low cost, simple operation Complex synthesis process Protein separation Monodisperse porous silica microspheres [ 58 , 62 , 63 ] Microfluidic electrospray Uniform size and good monodispersity Low production efficiency Skin wounds Novel drug-loaded methacryloyl chondroitin sulfate (CSMA) microspheres [67, 196] Spray drying Simple and stable Limited range of polymers Gastropathy Chitosan-based microspheres [ 75 ] Self-assembly method Simple production technology, mild reaction conditions, and suitability for hydrophilic and hydrophobic drugs Size and monodispersity need to be improved Oncotherapy Paclitaxel-loaded silk fibroin nanospheres [ 78 ] Phase separation method For water-soluble drugs, easy to prepare in batches Difficult to remove organic solvents Arthritis Loaded sPL sustained-release microspheres [ 206 ] Membrane emulsification method...…”
Section: Processing Methods Of Microspheresmentioning
confidence: 99%
“… Preparative ​technique Merits Demerits Application Microsphere-drug ​combination Ref. Emulsion-solidication Large-scale production, simple operation Wide particle size Oncotherapy Neuralrepair TPP/chitosan/PLGA-NGF Microspheres 5-Fluorouracil loaded biodegradable magnetic Microspheres Polysaccharidebased porous microsphere (PPM) [ 88 , 188 , 189 ] Microfluidics Unique analytical performance, smaller volume, good monodispersity Low production efficiency Oncotherapy 5-Fu loaded CS microspheres [ 30 , 35 ] Mold method Low cost, simple operation Complex synthesis process Protein separation Monodisperse porous silica microspheres [ 58 , 62 , 63 ] Microfluidic electrospray Uniform size and good monodispersity Low production efficiency Skin wounds Novel drug-loaded methacryloyl chondroitin sulfate (CSMA) microspheres [67, 196] Spray drying Simple and stable Limited range of polymers Gastropathy Chitosan-based microspheres [ 75 ] Self-assembly method Simple production technology, mild reaction conditions, and suitability for hydrophilic and hydrophobic drugs Size and monodispersity need to be improved Oncotherapy Paclitaxel-loaded silk fibroin nanospheres [ 78 ] Phase separation method For water-soluble drugs, easy to prepare in batches Difficult to remove organic solvents Arthritis Loaded sPL sustained-release microspheres [ 206 ] Membrane emulsification method...…”
Section: Processing Methods Of Microspheresmentioning
confidence: 99%
“…HA is the primary component of glycosaminoglycan in ECM. It consists of repeated disaccharide units of n-acetyl-D-glucosamine and β -D-glucuronic acid, alternately linked by β-1,4 and β-1,3 glycosidic bonds ( Graça et al, 2020 ; Li et al, 2021b ). Natural HA does not affect cell adhesion or gel formation.…”
Section: Materials Of Injectable Hydrogelsmentioning
confidence: 99%
“…PL is a natural GFs pool consisting of TGF-β1, TGF-β3, IGF-1, and VEGF and can be prepared by simple PRP thermal cycling. Due to the removal of platelet fragments by gradient centrifugation, the immunogenicity of PL is lower than that of PRP ( Li et al, 2021b ). Tang and his team encapsulated PL using EPL and heparin NPs into injectable hydrogels.…”
Section: Materials Of Injectable Hydrogelsmentioning
confidence: 99%
“…Combining microspheres and hydrogels improved the sustained drug-release properties for OA treatment for up to 99 days. Li et al 182 demonstrated that super-activated platelet lysate (sPL)-loaded PLGA/chitosan/gelatin microspheres improved the sustained drug release, inhibited osteoarthritis, and promoted cartilaginous repairs. Park et al 183 reported the utility of gelatin microspheres that are responsive to proteolytic enzymes typically expressed in arthritic flares, resulting in the on-demand and spatiotemporally controlled release of anti-inflammatory cytokines for cartilage preservation and repair.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%
“…The microspheres in vivo could also smooth the surface of cartilage. [ 182 ] PLGA Dexamethasone Slow release In vivo Dogs Cartilage repairing [ 181 ] GelMA and DMA-MPC DS Lubrication; Slow release In vitro & vivo Chondrocytes; Rats The microspheres had the characteristics of lubricity and sustained release so they could significantly up-regulate the expression level of cartilage anabolism genes and down-regulate the expression level of cartilage catabolism protease genes. [ 179 ] CS YAP-selective inhibitor Targeting In vitro & vivo Chondrocyte; Mice YAP could maintain the phenotype of chondrocytes and prevent cartilage degeneration in OA by targeting downstream molecular activity of ECM hardness.…”
Section: Different Drug-delivery Systems For Intra-articular Injectio...mentioning
confidence: 99%